Respuesta :
you would have to isolate the u variable:
y = 3/5u + 5
-5 -5
y-5=3/5u
__ ____
3/5 3/5
u= y-5
__
3/5
y = 3/5u + 5
-5 -5
y-5=3/5u
__ ____
3/5 3/5
u= y-5
__
3/5
An equation is formed of two equal expressions. In the given equation the value of u will be u=(5/3)(y - 5).
What is an equation?
An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
The given equation y=(3/5)u+5 can be solved for u as shown below,
y = (3/5)u + 5
Subtract 5 from both sides of the equation,
y - 5 = (3/5)u + 5 - 5
y - 5 = (3/5)u
Multiply both sides of the equation by 5/3,
(5/3)(y - 5) = (5/3) × (3/5)u
(5/3)(y - 5) = u
u = (5/3)(y - 5)
Hence, In the given equation the value of u will be u = (5/3)(y - 5).
Learn more about Equation here:
https://brainly.com/question/14686792
#SPJ5